Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Harga Terhadap Kepuasaan Pelanggan (Study Kasus Pada Pelanggan Kedai Sarijan Coffee Jl. Simpang Gajayana No 69 Kel. Merjosari Kec. Lowokwaru Kota Malang) - Ahmad Amirudin Masykuri; Afi Rahmat Slamet; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conducted at Kedai Sarijan Coffee Jl. Gajayana intersection No 69 Kel. Merjosari Kec. Lowokwaru Malang City. This type of research is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of service quality, product quality and price on customer satisfaction. The independent variables used are service quality, product quality and price, while the dependent variable is customer satisfaction. The sample used in this study were 78 respondents who were customers of Kedai Sarijan Coffee Jl. Gajayana intersection No 69 Kel. Merjosari Kec. Lowokwaru Malang City. The data collection technique used a questionnaire. The analysis method used is the instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using computer software SPSS 16.0 data processing. The results of this study indicate that service quality affects customer satisfaction, product quality affects customer satisfaction and price affects customer satisfaction. Service quality, product quality and price simultaneously affect customer satisfaction. Keywords: Service Quality, Product Quality, Price, Customer Satisfacti